Peranan Mohammad Hatta pada Masa Pemerintahan Parlementer 1948-1956 - Kasirun Kasirun; Iskandar Syah; Wakidi Wakidi (PESAGI (Jurnal Pendidikan dan Penelitian Sejarah), 2018)
This study aims to find out what role sisitem Mohammad Hatta during 1948-1956 Parliamentary government. The method used in this research is the methode of data collection using techniques historis. The data collecting were done by using literature technique and documantation technique, and the data analysis were done by using analysis and qualitative. Based on the research role during the reign of Mohammad Hatta Mohammad Hatta 1948-1956 parliamentary became Prime Minister, chairmandelegation of the Round Table Conference (RTC) and The originator of the Indonesian People's Economy.Penelitian ini bertujuan untuk mengetahui apa saja peranan Mohammad Hatta pada masa sisitem pemerintahan parlementer 1948-1956. Metode yang digunakan dalam penelitian ini adalah metode historis. Teknik pengumpulan data menggunakan teknik kepustakaan dan dokumentasi, untuk menganalisis data menggunakan analisis data kualitatif. Berdasarkan hasil penelitian peranan Mohammad Hatta pada masa pemerintahan parlementer 1948-1956 yaitu Mohammad Hatta menjadi perdana menteri, ketua delegasi Konferensi Meja Bundar (KMB) dan Penggagas Ekonomi Kerakyatan bagi Indonesia.Kata kunci: mohammad hatta, parlementer, pemimpin